Content of Volume 19 Issue 1 June 2023 - Interdental Jurnal Kedokteran Gigi (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Content of Volume 19 Issue 1 June 2023 SUB-ACUTE TOXICITY TEST OF RED GINGER EXTRACT (Zingiber officinale var. Rubrum) ON MICE (Mus musculus)Putu Sulistiawati Dewi, Mochammad Taha Ma’ruf1-5 THE EFFECT OF SMOKING HABITS ON THE OCCURRENCE OF BRUXISM: A RAPID REVIEWPrida Lani Debora P, Rasmi Rikmasari, Seto Pramudita6-10 TREATMENT OF HERPES ASSOCIATED ERYTHEMA MULTIFORME (HAEM)Raziv Ganesha, Rina Kartika Sari11-16 CORRELATION OF MOUTH BREATHING HABITS TO DENTAL MALOCCLUSIONSKetut Virtika Ayu, I Dewa Gede Budijanana, Norman Hidajah, Surwandi Walianto17-21 EARLY DETECTION OF VERRUCOUS CARCINOMA USING METHYLENE BLUE STAINING IN SUSPECTED LEUKOPLAKIA LESION: A CASE REPORTRina Kartika Sari, Raziv Ganesha, Esti Kurniawati22-28 RELATIONSHIP BETWEEN THE ANGLE OF INCLINATION OF THE MAXIMUM INCLINATION TO THE SOFT TISSUE OF THE FACIAL IN BALINESE WOMEN USING THE HOLDAWAY METHODNorman Hidajah, Dwis Syahrul, Ketut Virtika Ayu29-33 GEL GEL EXTRACTION OF EARTHWORMS (Lumbricus rubellus) TO THE NUMBER OF FIBROBAL CELLS IN MALE WISTAR RATS (Rattus norvegiccus) GINGIVAL WOUND HEALINGNi Wayan Arni Sardi, Ni Luh Putu Sri Maryuni Adnyasari, Ni Putu Ratih Berliana Ekasari34-42 THE USE OF CHLORHEXIDINE MOUTHWORKS CAN REDUCE THE ACCUMULATION OF DENTAL PLAK IN USERS OF FIXED ORTHODONTICDEVICESDwis Syahrul, Surwandi Walianto, Priscilla Sonia Suwongto43-48 EFFECTIVENESS OF RED BITES FRUIT (Beta vulgaris) AS A MOUTH MOUTH TO REDUCE HALITOSISI Gusti Ngurah Putra Dermawan, Intan Kemala Dewi, Fritz Gerald Dharma Tedjamartono49-54 PLAQUE CONTROL IN PERIODONTAL DISEASENi Luh Putu Sri Maryuni Adnyasari, Dwis Syahriel , I.G.A Dewi Haryani55-61 ERUPTION CYST OVERLYING THE CROWN OF UPPER RIGHT FIRST PREMOLAR: A CASE REPORTWayan Sutresna Yasa, Kirana Guspiari, I Made Hendra Cahyadita Nusantara Putra62-66 LD50 ACUTE TOXICITY TEST OF GREEN GRASS JELLY (Cyclea barbata Miers) LEAF EXTRACT AGAINST MICE (Mus musculus L.)Hendri Poernomo, Mochammad Taha Ma’ruf, Ari Sucitra Dewi67-73